The effect of covert narcissism on workplace incivility: the mediating role of self‐esteem and norms for respect - Moon, Chanki (2022)
There has been an abundance of research on narcissism in the workplace. However, most research has focused on the overt (grandiosity) form of narcissism, as well as the effect of narcissism on uncivil behaviors of employees; research focusing directly on the effect of covert (vulnerability) narcissism on the employees’ experience of workplace incivility is lacking. The present research examined whether the personality trait (covert narcissism) of employees affects their experience of incivility considering two potential explanatory variables: self-esteem and perceived norms for respect. A total of 150 participants completed an online questionnaire, which consisted of four well-known measures: the Hypersensitive Narcissism Scale, the Rosenberg Self-esteem scale, the Perceived Norms for Respect, and the Workplace Incivility Scale. The results showed that employees with higher levels of covert narcissism are likely to have greater experiences of workplace incivility through the mediating role of perceived norms for respect. Although the relationship was not explained through the mediating role of self-esteem, it was instead observed that self-esteem and perceived norms for respect jointly affect employees’ experience of incivility at work. These findings broaden our understanding of workplace incivility by simultaneously considering the influences of personality traits, self-esteem, and workplace norms.